Refuse in order to resist: metabolic bottlenecks reduce antibiotic susceptibility - Orestis Kanaris; Frank Schreiber (Molecular Systems Biology)
The growth of pathogenic bacteria in the host is a prerequisite for infectious diseases. Antibiotic drugs are used to impair bacterial growth and thereby treat infections. In turn, growth of bacteria is underpinned by their primary metabolism. Thus, it has long been recognized that the activity of antibiotics is determined by the metabolic state of cells. However, only recently researchers have begun to systematically interrogate the links between metabolism and resistance (Jiang et al, 2023; Lopatkin et al, 2021; Pinheiro et al, 2021; Schrader et al, 2021; Zhao et al, 2021). In their recent study, Lubrano and colleagues (Lubrano et al, 2025) apply an elegant CRISPR-based approach to the model bacterium Escherichia coli to systematically screen the effect of 15,120 mutations in genes that encode for 346 proteins which are required for growth of E. coli (also referred to as ‘essential proteins’). The authors identified a multitude of mutations that reduce the susceptibility against two antibiotics related to two very distinct chemical classes; the β-lactam antibiotic carbenicillin and the aminoglycoside gentamicin. Strikingly, the majority of the identified mutations are directly linked to primary metabolism. The work highlights the importance of metabolism in order to understand antibiotic resistance mechanisms and the ecology and evolution of antibiotic resistance. In addition, the work provides leads to design metabolism-based intervention strategies to mitigate antibiotic resistance.